Maize Streak Virus: diversity and virulence - Martin, Darren Patrick (Department of Molecular and Cell Biology, 2014)
Zea mays was first introduced to Africa in Ghana by Portuguese traders in the 16th century. The steady spread of maize cultivation since then has made it the most important cereal crop in Africa today. Whereas improved maize genotypes and agricultural techniques enable yearly yields above 10 tons hectare-1 in the developed world, yearly yields across Africa have remained low at about 1 ton hectare-1 in most countries. Although outmoded agricultural practices are the main reason for poor yields, maize pathogens inflict substantial additional losses. Of the many pathogens currently confronting maize farmers in Africa, Maize streak virus (MSV) is the most significant.